ONTOLOGI KEBENARAN DALAM PENDIDIKAN ISLAM: PERSPEKTIF INTEGRATIF ANTARA RASIO, WAHYU DAN TEKNOLOGI - Adang Hambali; Rizki Imanudin; Rizqynursholihat; Dayat Indra Hidayat; Dede Sulaeman (Tadbir: Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to analyze the ontology of truth in Islamic education through an integrative perspective between reason, revelation, and technology. This research employs a qualitative method with a library research approach, examining both classical and contemporary sources relevant to Islamic epistemology and the philosophy of education. The findings reveal that in Islamic education, truth does not solely originate from human reason, which is empirical, but also from divine revelation as an absolute and transcendental foundation. The integration of reason and revelation provides an epistemological basis capable of creating a balanced educational system between intellect and faith. In the digital era, technology serves as an instrument to expand the reach of knowledge and enhance the effectiveness of learning, yet its use must remain guided by the principles of tawhid and Islamic ethics. This study emphasizes the importance of a scientific paradigm that harmonizes rational, spiritual, and technological dimensions to construct Islamic education that is humanistic, adaptive, and oriented toward holistic truth.